Business Model Formulation of Social-Commerce Based Influencer on Instagram Platform - Bisma, M. Ardhya; Pramudita, Aditia Sovia (Jurnal Organisasi dan Manajemen, 2021)
The growth of ICT in Indonesia has led to various new business models, one of which is the Influencer business model. Influencer is a business that focuses on generating opinions on a product or service. Influencers have become a trend in Indonesia, especially on the Instagram platform. Given that influencers are a new business model, there is still no standard business model in this industry. This study aims to map the social-commerce based influencer business model on the Instagram platform in Indonesia. This research is qualitative in nature. Data were collected by interviewing companies that have a focus on influencer and social-commerce business. Business model mapping is done using value chain analysis and business model canvas. Based on the research results, it is found that social-commerce based influencers must be able to divide their value propositions, channels, customer relationships, and consumer segments into two types, namely audiences and advertisers. This division of consumer types is very important in the social-commerce based influencer business considering influencers get revenue through advertisers and the power to influence audience to buy the endorsed product.